PHARMACOGENOMIC ANALYSIS OF SNPs OF ACE GENE IN STROKE - Patil, Maheswari L; Patel, Seema J (Asian Journal of Pharmaceutical and Clinical Research, 2015)
The commonly occurring neurological disorder is stroke disease, which is a third largest killer in the world. Study of genes involved to cause stroke is one of the way to find drugs for prevention or treatment of stroke. The purpose of the present study is to develop therapeutics by giving individualized medicine based on significant single-nucleotide polymorphisms (SNPs) involved in the pathogenesis of disease. Genome-wide association approach scans the entire genome looking through thousands of genetic variants SNPs with an aim to discover novel gene associated with a specific disease. In the present study, the most intensively investigated candidate gene is angiotensin-I converting enzyme (ACE). The normal and mutated forms of ACE gene are selected, and the active site of predicted protein structure is identified where the selected ligand binds. The selected ligands of both existing and modified molecules were docked with predicted protein using AutoDock tool. The docking results were analyzed based on the maximum number of hydrogen bond interactions. The results predicted that anti-hypertensives, anticoagulants, tissue plasminogen activators (TPAs) have strong interaction with stroke genes. The docking studies showed that ACE gene strongly interacts with r-TPA and is used for treatment of strokes. Keywords: Stroke, Single-nucleotide polymorphism, Angiotensin-I converting enzyme, Individualized medicine.